Seeds of change: transforming african agriculture together-Dr Bernard Comoe - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
Following the visit of the delegates from Côte d’Ivoire to IITA, Dr. Bernard Comoe' from Côte d’Ivoire shared key outcomes from the World Bank–funded agricultural mission. The team explored innovations in seeds, breeding, cassava, horticulture, and aquaculture value chains. With $250M already invested, they aim to strengthen research, extension, and entrepreneurship capacities. Four partnership areas were identified, and actions are already underway—including MoUs and lab support for digital transformation and agri-entrepreneurship.